Effect of Co-infection of Low Pathogenic Avian Influenza H9N2 Virus and Avian Pathogenic E. coli on H9N2-Vaccinated Commercial Broiler Chickens - Mahmoud, Sherif I. A.; Zyan, Kamel A.; Hamoud, Mohamed M.; Khalifa, Eman; Dardir, Shahin; Khalifa, Rabab; Kilany, Walid H.; Elfeil, Wael K. (Frontiers in Veterinary Science, 2022)
In the last 40 years, low pathogenic avian influenza virus (LPAIV) subtype H9N2 has been endemic in most Middle Eastern countries and of course Egypt which is one of the biggest poultry producers in the middle east region. The major losses with the H9N2 virus infections come from complicated infections in commercial broiler chickens, especially E. coli infection. In this work, 2,36,345 Arbor acres broiler chickens from the same breeder flock were placed equally in four pens, where two pens were vaccinated against LPAIV of subtype H9N2 virus, and the other two pens served as non-vaccinated controls. All were placed on the same farm under the same management conditions. A total of twenty birds from each pen were moved to biosafety level−3 chicken isolators (BSL-3) on days 21 and 28 of life and challenged with LPAIV-H9N2 or E. coli. Seroconversion for H9N2 was evaluated before and after the challenge. The recorded results revealed a significant decrease in clinical manifestations and virus shedding in terms of titers of shedding virus and number of shedders in vaccinated compared to non-vaccinated chickens. In groups early infected with LPAIV-H9N2 virus either vaccinated or not vaccinated, there was no significant difference in clinical sickness or mortalities in both groups, but in late infection groups with H9N2 alone, non-vaccinated infected group showed significantly higher clinical sickness in comparison with infected vaccinated group but also without mortality. In groups co-infected with E. coli (I/M) and H9N2, it showed 100% mortalities either in vaccinated or non-vaccinated H9N2 groups and thus reflect the high pathogenicity of used E. coli isolates, whereas in groups co-infected with E. coli (per os to mimic the natural route of infection) and LPAIV-H9N2, mortality rates were significantly higher in non-vaccinated groups than those vaccinated with H9N2 vaccine (15 vs. 5%). In conclusion, the use of the LPAIV H9N2 vaccine has significantly impacted the health status, amount of virus shed, and mortality of challenged commercial broilers, as it can minimize the losses and risks after co-infection with E. coli (orally) and LPAIV-H9N2 virus under similar natural route of infection in commercial broilers.